Kehidupan Masyarakat Multikultur di Dusun Wanasari Desa Dauh Puri Kaja Denpasar Utara 1982-2019 - Angreini, Rani; Wirasmini Sidemen, Ida Ayu; Inten Asmariati, Anak Agung (Humanis; Vol 25 No 3 (2021)DO - 10.24843/JH.2021.v25.i03.p16, 2021)
Dusun Wanasari is one of the hamlets where a multicultural society develops and makes the people of Wanasari Hamlet create harmony with the people in Denpasar. The people of Wanasari Hamlet were originally market people from various regions in Indonesia who lived and traded around the Payuk market area. The establishment of Wanasari Hamlet was based on the land given by Cokorda Pemecutan because the number of people living in the Payuk market area was increasing from time to time. The social development that occurs in Wanasari Hamlet is increasing every year and bringing about changes. This can be seen from the population that grows every year, followed by the development of traditions, arts, and the community's economy. The purpose of this study was to determine the background of the establishment of Wanasari Hamlet, diversity and acculturation, as well as the implications of diversity for the lives of the people of Wanasari Hamlet.